Comparative study of propofol and dexmedetomidine Infusion for hypotensive anesthesia in FESS surgeries: A randomized prospective double-blind controlled study - Anesa Syed,; Virshid, Rajashri; Phaphagire, Nikita; Anjum, Naved (Asian Journal of Medical Sciences, 2023)
Background: Intra operative bleeding is most common factor that diminishes visibility resulting in an increased incidence of complications in patients undergoing functional endoscopic sinus surgery (FESS). Methods to reduce intra-operative bleeding include Trendelenburg position, maintenance of normothermia, and controlled hypotension by various anesthetic techniques. Many studies have shown that propofol and dexmedetomidine infusion reduces the amount of bleeding in different surgeries. Aims and Objectives: The aim of the study was to compare the effects of dexmedetomidine and propofol infusion over hemodynamic, quantity of blood loss, and quality of surgical field in patients undergoing FESS and to compare the side effects of dexmedetomidine and propofol infusion in cases undergoing FESS. Materials and Methods: This was a comparative study conducted in the department of anesthesiology of a tertiary care medical college. The duration of study was 2 years. 60 patients of ASA Grades I and II with age between 20 and 60 years, including both males and females posted for FESS were included in this study on the basis of a predefined inclusion and exclusion criteria. Patients were divided into two groups (on the basis of whether they received propofol or dexmedetomidine infusion) of 30 patients each. Hemodynamic parameters (Heart rate and mean arterial pressure [MAP]) quantity of blood loss, quality of surgical field, and side effects were recorded and compared in both the groups. For statistical purposes, P<0.05 was taken as statistically significant. Results: Antrochoanal polyp and chronic sinusitis were the most common indication of FESS in studied cases. Intraoperatively, heart rate was lower in both the groups as compared to baseline. However, the heart rate was lower in the Group D at all times as compared to Group P and the difference was statistically significant from 20 min onward after induction. The mean arterial blood pressure in both the groups was comparable till up to 15 min post induction with no statistical difference. Thereafter, the mean arterial blood pressure was lower in Group D than in Group P throughout the procedure, the difference being statistically significant (P<0.05). The isoflurane requirement in Group D was significantly lower starting from 5 min of induction to throughout the procedure as compared to Group P (P< 0.05). Mean blood loss in Group D was 115.0±16.78 ml and in Group P was 140.47±29.42 ml, the difference in blood loss was statistically significant (P<0.0001). Conclusion: Dexmedetomidine is comparatively better than propofol in controlling heart rate and MAP, reducing the blood loss, and isoflurane requirement in patients undergoing FESS.